2011
DOI: 10.3109/0886022x.2011.618920
|View full text |Cite
|
Sign up to set email alerts
|

Chloroform Poisoning – A Case Report

Abstract: Chloroform, a halogenated hydrocarbon, causes central nervous system (CNS) depression, cardiac arrhythmias, hepatotoxicity, and renal failure. We describe a successful outcome in a case of chloroform ingestion with renal and hepatotoxicity with N-acetylcysteine (NAC) administration and hemodialysis support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 6 publications
0
14
0
1
Order By: Relevance
“…Some studies showed the cardiac effects of halogenated hydrocarbons . In this study, workers exposed to organic and halogenated solvents too.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Some studies showed the cardiac effects of halogenated hydrocarbons . In this study, workers exposed to organic and halogenated solvents too.…”
Section: Discussionmentioning
confidence: 82%
“…2,3 Some studies showed the cardiac effects of halogenated hydrocarbons. 13 In this study, workers exposed to organic and halogenated solvents too. Another study showed the mechanisms involved in cardiac sensitization by halogenated hydrocarbons.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Typically, the following four THMs are found as a result of chlorination: trichloromethane (TCM), bromodichloromethane (BDCM), dibromochloromethane (DBCM) and tribromomethane (TBM). These groups of compounds have been implicated in liver and kidney defects, central nervous system problems, cardiac arrhythmias and increased risk of carcinogenicity and mutagenicity as Class B carcinogens [5] [6] [7].…”
Section: Introductionmentioning
confidence: 99%
“…3 Chloroform-induced hepatotoxicity is usually delayed, with transaminase levels peaking at 48-72 h post-exposure and returning to normal over 4-6 weeks. [2][3][4][5] There are published case reports of toxicity occurring after ingestion or inhalational exposure, but no reports of dermal chloroform exposure resulting in systemic toxicity.…”
mentioning
confidence: 99%